Pemanfaatan Virtual Reality sebagai Media Pembelajaran Perakitan Komputer - Ridwan Zulkifli; Egi Lukman Nurhakim; Rika Setiani Nur Faidah; Rike Setiani Nur Fadillah; Umi Lutfiatul Fadilah; Nur Kesha Sophiawati; Devi Perdiansyah; Derismana Derismana; Dzikri Alfathurrahman (2026)
Abstrak - Keterbatasan fasilitas Teknologi Informasi dan Komunikasi di sekolah menengah kejuruan menjadi kendala dalam pembelajaran perakitan komputer yang bersifat praktik. Penelitian ini bertujuan mengembangkan media pembelajaran perakitan komputer berbasis Virtual Reality sebagai solusi alternatif untuk meningkatkan keterlibatan dan pemahaman siswa. Aplikasi dikembangkan menggunakan game engine Unity dengan metode Multimedia Development Life Cycle yang meliputi tahap konsep, perancangan, pengumpulan bahan, perakitan, pengujian, dan distribusi. Media pembelajaran ini dijalankan pada perangkat Android dan didukung oleh VR Box sehingga memungkinkan siswa berinteraksi dengan komponen komputer secara virtual dalam lingkungan tiga dimensi. Evaluasi sistem dilakukan melalui alpha testing menggunakan black box testing serta beta testing dengan User Acceptance Testing menggunakan skala Likert terhadap 27 siswa jurusan Teknik Komputer dan Jaringan. Hasil pengujian menunjukkan tingkat penerimaan pengguna sebesar 81% dengan kategori sangat diterima. Hal ini menunjukkan bahwa media pembelajaran berbasis Virtual Reality mampu menjadi alternatif pembelajaran praktikum yang efektif serta membantu siswa memahami proses dan komponen perakitan komputer meskipun tanpa perangkat fisik secara langsung.Kata kunci : Virtual Reality; Media Pembelajaran; Perakitan Komputer; Sekolah Menengah Kejuruan; Abstract - Lecturer research management in higher education institutions often faces complex administrative challenges that are time-consuming and prone to documentation errors. These problems include difficulties in tracking proposal status, inconsistent progress reporting, and lack of transparency in the review process. The purpose of this study is to evaluate the effectiveness of a throwaway prototyping-based development approach in building a lecturer research management information system that is usable, efficient, and capable of improving administrative productivity. The system is designed to simplify research administration activities, such as proposal submission, reviewer assignment, progress reporting, and integrated research output tracking. The study employs a mixed method design that combines quantitative approaches through usability and time efficiency measurements, as well as qualitative approaches through in-depth interviews. The development process applies a throwaway prototyping cycle through stages: (1) initial requirements identification through stakeholder analysis, (2) rapid prototype creation for concept validation, (3) iterative evaluation and validation with end users, (4) prototype disposal and final system implementation based on feedback. This approach was chosen to accelerate requirements elicitation, validate interface flows before full development, and minimize rework before final implementation. The system was implemented as a web application using PHP (Laravel) and a relational database. Usability evaluation was conducted using the System Usability Scale (SUS), complemented by task-based efficiency measurements and brief interviews with end users. The research results show an SUS score of 85.5, indicating excellent usability and high user acceptance. Task completion time for core administrative activities decreased by 35% compared to manual processes. Qualitative feedback shows improved status transparency, reduced administrative burden, and more consistent documentation. Overall, these findings demonstrate that the prototyping model is effective for developing research management systems in higher education, particularly when user feedback is integrated from the outset and conducted iteratively.Keywords: Virtual Reality; Learning Media; Computer Assembly; Vocational High School;